2018
DOI: 10.1112/s0010437x17007710
|View full text |Cite
|
Sign up to set email alerts
|

Motivic and real étale stable homotopy theory

Abstract: Let S be a Noetherian scheme of finite dimension and denote by ρ ∈ [½, Gm] SH(S) the (additive inverse of the) morphism corresponding to −1 ∈ O × (S). Here SH(S) denotes the motivic stable homotopy category. We show that the category obtained by inverting ρ in SH(S) is canonically equivalent to the (simplicial) local stable homotopy category of the site S rét , by which we mean the small realétale site of S, comprised ofétale schemes over S with the realétale topology.One immediate application is that SH(R)[ρ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 37 publications
2
77
0
Order By: Relevance
“…Morel proved a version of Gabber rigidity theorem for a cohomology theory representable in the motivic stable homotopy category by an n-torsion spectrum provided that the base field satisfies a certain assumption on the finiteness of the virtual cohomological 2-dimension. The latest rigidity result was obtained by Bachmann [Ba16,Corollary 40] as a corollary of his study of ρ-inverted stable motivic homotopy category by means of realétale topology. Bachmann showed that a version of Gabber rigidity theorem holds for a cohomology theory representable by a ρ-periodic spectrum with ρ = −[−1] ∈ K MW 1 (k) ∼ = Hom SH(k) (S, S ∧ (A 1 − {0}, 1)).…”
Section: Introductionmentioning
confidence: 99%
“…Morel proved a version of Gabber rigidity theorem for a cohomology theory representable in the motivic stable homotopy category by an n-torsion spectrum provided that the base field satisfies a certain assumption on the finiteness of the virtual cohomological 2-dimension. The latest rigidity result was obtained by Bachmann [Ba16,Corollary 40] as a corollary of his study of ρ-inverted stable motivic homotopy category by means of realétale topology. Bachmann showed that a version of Gabber rigidity theorem holds for a cohomology theory representable by a ρ-periodic spectrum with ρ = −[−1] ∈ K MW 1 (k) ∼ = Hom SH(k) (S, S ∧ (A 1 − {0}, 1)).…”
Section: Introductionmentioning
confidence: 99%
“…We thus need to establish condition 5. We do this in some detail; this style of argument can also be used to make more precise our sketches for conditions [1][2][3][4]…”
Section: Given Morphismsmentioning
confidence: 99%
“…Let ρ denote the map ½ → Σ α ½ induced by taking the nonbasepoint of S 0 to −1 ∈ A 1 0. In [3], Bachmann finds an alternate presentation of the ρinverted stable motivic homotopy category SH A 1 (F )[1/ρ] in terms of the real étale topology. We will not go into the details of the real étale topology, instead sending the reader to [25], especially its first chapter.…”
Section: Bachmann's Theoremmentioning
confidence: 99%
“…We solve this problem using Bachmann's theorem on π ⋆ ½[1/2, 1/η] and the Hu-Kriz-Ormsby comparison of the 2-and (2, η)-complete spheres when F has finite virtual 2-cohomological dimension. 3 In order to state our results, let π top m ½ denote the m-th homotopy group of the topological sphere spectrum. Theorem 1.5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation